2021
DOI: 10.1038/s41598-021-90412-2
|View full text |Cite
|
Sign up to set email alerts
|

Axonopathy precedes cell death in ocular damage mediated by blast exposure

Abstract: Traumatic brain injuries (TBI) of varied types are common across all populations and can cause visual problems. For military personnel in combat settings, injuries from blast exposures (bTBI) are prevalent and arise from a myriad of different situations. To model these diverse conditions, we are one of several groups modeling bTBI using mice in varying ways. Here, we report a refined analysis of retinal ganglion cell (RGC) damage in male C57BL/6J mice exposed to a blast-wave in an enclosed chamber. Ganglion ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…The significant decrease in the percent of Brn3a-negative RBPMS-positive RGCs we observed from 1 to 6 months of age (from 9.77% at 1 month to 6.44% at 6 months), is consistent with prior studies by Boehme et al who showed that 8.9% of Brn3a-negative RBPMS-positive RGCs were observed in 13 to 17-week-old mice. 32 After 6 months of age, we found no significant change in the percent of RBPMS- and Brn3a-positive RGCs, as RBPMS antibodies consistently stained RGCs that Brn3a antibodies did label, in agreement with previous studies. 14 The decrease in the percent of Brn3a-negative RBPMS-positive cells could be due to changes in protein degradation leading up to 6 months of age, or that RBPMS-positive and Brn3a-negative RGCs tend to die first with age.…”
Section: Discussionsupporting
confidence: 92%
“…The significant decrease in the percent of Brn3a-negative RBPMS-positive RGCs we observed from 1 to 6 months of age (from 9.77% at 1 month to 6.44% at 6 months), is consistent with prior studies by Boehme et al who showed that 8.9% of Brn3a-negative RBPMS-positive RGCs were observed in 13 to 17-week-old mice. 32 After 6 months of age, we found no significant change in the percent of RBPMS- and Brn3a-positive RGCs, as RBPMS antibodies consistently stained RGCs that Brn3a antibodies did label, in agreement with previous studies. 14 The decrease in the percent of Brn3a-negative RBPMS-positive cells could be due to changes in protein degradation leading up to 6 months of age, or that RBPMS-positive and Brn3a-negative RGCs tend to die first with age.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous data support continuing retinal ganglion cell loss as a result of optic nerve injury up to 30 DPI, but we have yet to analyze retinal samples past this time point. Depending on the injury type and severity, studies utilizing diffuse TAI fluid percussion [ 42 ], ultrasound [ 43 ], blast [ 44 , 45 ] or optic nerve crush/stretch models [ 46 , 47 , 48 ] disagree on the time course or presence of RGC death ranging from no RGC loss or showing persistent dieback up to 3 months post injury. Furthermore, recent chronic human studies show that the retina progressively thins up to 35 years after injury implying long-term RGC death [ 15 ], which will be crucial to characterize in future studies of TON.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be that too many RGCs were lost by 7 DPI to detect any significant changes in ER stress, which could have resolved to eliminate all the injured cells by 7 days. We cannot say this conclusively, though, because we have not yet identified the time point of maximal cell loss in either of these models, and there are wide ranges reported in the TBI literature (Boehme et al, 2021;Bricker-Anthony et al, 2014;Guley et al, 2016a;Harper et al, 2019;Jha et al, 2018;Patel et al, 2017;Struebing et al, 2018).…”
Section: Discussionmentioning
confidence: 92%